High plasma H2O2 level and low plasma catalase level as risk factors for acne vulgaris - Anak Agung Gde Putra Wiraguna; Made Wardhana; Made Kusuma Dewi Maharani (DiscoverSys Inc, 2019)
Background: In this recent time, ROS and oxidative stress have been said to play an important role in the pathogenesis of inflamed acne lesions. One example of ROS produced by neutrophil through phagocytosis is H2O2. Nevertheless, there is an enzymatic antioxidant which catalyses H2O2 called catalase. Imbalance of free radicals and antioxidants due to excessive ROS formation promotes the state of oxidative stress and inflammation of the acne lesion.Objective: This study aimed to determine plasma H2O2 and catalase level as a risk factor for acne.Methods: This matched-pair case-control observational analytic study involving 38 patients with acne and 38 patients without acne. Sampling was done using consecutive sampling which fulfils the inclusion and exclusion criteria and followed by matching with age and gender. H2O2 and catalase level measured on both groups. The analysis was done using SPSS.Results: H2O2 mean level in the case and control group, respectively 0.68 ± 0.03 and 0.42 ± 0.04 µmol/ml. High H2O2 level was determined from cut-off point >0.62 µmol/ml. High H2O2 was a statistically significant risk factor for acne vulgaris (p<0.001; 95% CI: 4.59-40.62; OR: 13.67). The mean level of catalase in the case and control group respectively 0.48 ± 0.06 and 0.74 ± 0.07 U/ml. Low catalase level was determined from the cut-off point <0.58 U/ml. Catalase was significant risk factor for acne vulgaris (p<0.001; 95% CI: 5.18-77.21; OR: 20.00).Conclusion: High levels of H2O2 plasma and low levels of catalase plasma is a risk factor of acne vulgaris.